The Impact of Energy Prices on the Performance of Banks in Türkiye - Evci, Samet; Kefe, İrem and Kefe, İlker (International Journal of Energy Economics and Policy, 2024)
The aim of this study is to identify the direct and indirect effects of energy price changes on the financial performance of commercial banks operating in Türkiye. In this context, the impact of energy price changes on the return on assets and return on equity of 21 commercial banks operating between 2003 and 2022 is analyzed using the bias-corrected least-squares dummy variable (LSDVC) estimator. The model includes bank-specific variables such as net interest margin, the capital adequacy ratio, the ratio of total loans and receivables to total assets, the ratio of liquid assets to total assets, and the ratio of non-interest income to total assets. To identify indirect effects, macroeconomic variables such as gross domestic product and inflation rates are also included in the model. The findings reveal that energy prices have a direct and positive effect on the return on assets of banks, while showing no effect on return on equity. Given the limited studies examining the impact of energy price changes on the Turkish banking sector, the findings of this study may be beneficial in formulating measures and regulations regarding the stability of the banking sector.